Creating Purchasing Decisions Through the Role of Brand Awareness, Promotion and Distribution Channels (A Study on PALMIA Margarine Products in Ambon City) - Victor Ernest Huwae (Sean Institute, 2026)
This study aims to determine the influence of brand awareness, promotion and distribution channels on Palmia margarine purchasing decisions in Ambon City. The method used was quantitative descriptive with a purposive sampling technique to 100 respondents who had purchased and consumed Palmia margarine. Data collection was carried out through questionnaires and analyzed using multiple linear regression. The results of the study at a significance level of 5% show that: (1) Brand Awareness has a positive and significant effect on Purchasing Decisions, as evidenced by the t-count value of 2.953 with a significance value of 0.004 smaller than 0.05 (0.004<0.05), then (2) Promotion has a positive and significant effect on Purchasing Decisions, as evidenced by the t-count value of 3.437 with a significance value of 0.001 (0.001,<0.05) and (3) Distribution Channels have a positive and significant effect on Purchasing Decisions, as evidenced by the t-count value of 2.589 with a significance value of 0.011 (0.011<0.05).